Ta rutʻ Praññʻ svāʺ mhatʻ tamʻʺ : kuiyʻ tveʹ Ta rutʻ Praññʻ nhaṅʻʹ cā pe loka - Moṅʻ Moṅʻ Ññui (Bhāratī Cā pe : Guṇʻ thūʺ Cā pe mha praññʻ luṃʺ kvyatʻ phranʻʹ khyi saññʻ, 1992)
Travel impressions of a Burmese writer and medical doctor, while on a cultural delegation with other Burmese writers to Yunnan Province, China.